Risk stratification in differentiated thyroid cancer with RAI-avid lung metastases. Issue 8 (26th July 2021) - Ohkuwa, Keiko; Sugino, Kiminori; Nagahama, Mitsuji; Kitagawa, Wataru; Matsuzu, Kenichi; Suzuki, Akifumi; Tomoda, Chisato; Hames, Kiyomi; Akaishi, Junko; Masaki, Chie; Ito, Koichi
Abstract : Objective: Radioactive iodine (RAI) therapy is effective for differentiated thyroid cancer (DTC) patients with lung metastasis. However, some patients have a poor prognosis despite the RAI accumulation. The utility of inflammatory biomarkers, including neutrophil-to-lymphocyte ratio (NLR), has been reported as a prognostic factor for many carcinomas. This study aimed to investigate the risk factors related to DTC patient survival with RAI-avid lung metastasis and to attempt risk stratification. Design and methods: This retrospective study included 123 patients with RAI-accumulating lung metastatic DTC. The cause-specific survival (CSS) rate from the time of detection of lung metastasis was tested using the Kaplan–Meier log-rank test, and the multivariate analysis was calculated using the Cox proportional hazards model. NLR was retrospectively calculated using the blood sample collected before initial RAI treatment. The NLR cutoff value was 2.6 on the ROC curve. Results: Age ≥ 55 years at the time of operative treatment, follicular carcinoma, lung metastasis tumor ≥ 10 mm in diameter, age ≥ 55 years at the time of detection of lung metastasis, age ≥ 55 years at the time of RAI treatment, and NLR ≥ 2.6 at the initial RAI treatment were predictive of decreased CSS. Multivariate analysis identified that the independent prognostic factors were lung metastatic tumor ≥ 10 mm in diameter and NLR ≥ 2.6. Patients in the high-risk group with both factors had significantly lower CSS rates than those in the low- and intermediate-risk groups with one or none of these factors. Conclusions: The high-risk group patients had significantly poorer survival, and these patients could be considered as future candidates for tyrosine kinase inhibitor therapy.